UJI AKTIVITAS ANTIFUNGI KOMBINASI EKSTRAK UMBI BAWANG PUTIH (Allium sativum L) DAN DAUN SIRIH MERAH (Piper ornatum N.E.Br) TERHADAP PERTUMBUHAN Candida albicans - Artadevy, Nadhila Fahira; Daskar, Annajim; Suswidiantoro, Vicko; Safutri, Wina (Universitas Imelda Medan, 2025)
Candida infection caused by Candida albicans is a common health problem, especially in the skin and female reproductive organs. In Indonesia, the prevalence of candidiasis is around 20–25%, with a predominance in the hair, skin, mucous membranes, mouth, and esophagus. In Lampung Province, candidiasis incidents include severe intertrigo (56%), mild intertrigo (44%), axillary candidiasis (52%), and breast candidiasis (20%). This study aimed to evaluate the antifungal activity of a combination of garlic bulb (Allium sativum L.) and red betel leaf (Piper ornatum N.E.Br) extracts against the growth of Candida albicans. This study used a laboratory experimental method with a Completely Randomized Design (CRD), consisting of a negative control (distilled water), a positive control (fluconazole), and a combination of extracts with a ratio of 20%:20%, 20%:40%, and 40%:40%. The extract was obtained through maceration method, and antifungal activity was measured based on the inhibition zone. Phytochemical tests showed the presence of active compounds such as saponins, flavonoids, alkaloids, tannins, and steroids that act as antifungals. The results of the disc diffusion test showed the average diameter of the inhibition zone as follows: 0 mm (negative control), 6.49 ± 1.05 mm (positive control), 2.9 ± 0.26 mm (P1, weak), 4.15 ± 1.57 mm (P2, weak), 5.68 ± 2.73 mm (P3, moderate), and 6.81 ± 1.92 mm (P4, moderate). Statistical tests showed significant differences between negative and positive controls and treatments 2 and 3. In conclusion, the combination of garlic and red betel leaf extract, especially P4, has antifungal potential against Candida albicans.